Applied research on dairy cattle feeding systems in Colombian high tropics - Castillo, Javier; Benavides, Juan; Vargas, Juan; Avellaneda, Yesid; García, Gustavo (Revista de Ciencias Agrícolas, 2019)
Sustainable intensification of dairy production is a strategy to consolidate a competitive sector. However, technologies adoption is limited due to the difficulty to accessing to research results. The objective of this document was to review a compilation of research works carried out mainly by the Colombian Agricultural Research Corporation (Agrosavia) in specialized dairy feeding systems of Colombian high tropics. In soils issue, research has been carried out on soil recovery and grassland renewal. Recently, the growth of grasses has been evaluated under different environmental conditions to generate efficient forage management schemes. In 2018 was registered Altoandina oat to forage use, but, in Colombian high tropic, there is a limited offer to forages due to absence of breeding program and evaluation of germplasm. Integrated management of Collaria scenica has been developed. Characterization and use of tree and shrub species have been carried out to silvopastoral systems (SSPs). In feeding systems, Agrosavia has been working on determining chemical and nutritional compositional of feed resources and design of supplementation schemes to improve animal response. Methane production increases when mature forage species are used, contrary a balanced diet or grazing in SSPs reduces methane emissions. Finally, research developments must incorporate and recognize the production costs of the system to ensure the adoption of technologies.